PERAN POSITIVE EMOTION MEMEDIASI PENGARUH SALES PROMOTION DAN HEDONIC CONSUMPTION TERHADAP IMPULSE BUYING - Putri, Putu Indy Widiananda; Andani, I Gusti Agung Ketut Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Based on the results of a survey in 6 major cities in Indonesia, Lazada is not the public's top priority in making online purchases. The purpose of this study was to analyze the role of positive emotion in mediating the effect of sales promotion and hedonic consumption on impulse buying for Lazada customers. This research was conducted in Denpasar with 130 respondents determined by purposive sampling. Data was collected using questionnaire measured by Likert scale. Data analysis using PLS-based SEM. The results showed that sales promotion, hedonic consumption, and positive emotions had positive and significantly affecting impulse buying. Sales promotion woth hedonic consumption have positive and significantly affecting positive emotion, also positive emotions significantly mediates the relationship between sales promotion and hedonic consumption on impulse buying. Based on the results of a survey in 6 major cities in Indonesia, Lazada is not the public's top priority in making online purchases. The purpose of this study was to analyze the role of positive emotion in mediating the effect of sales promotion and hedonic consumption on impulse buying for Lazada customers. This research was conducted in Denpasar with 130 respondents determined by purposive sampling. Data was collected using questionnaire measured by Likert scale. Data analysis using PLS-based SEM. The results showed that sales promotion, hedonic consumption, and positive emotions had positive and significantly affecting impulse buying. Sales promotion woth hedonic consumption have positive and significantly affecting positive emotion, also positive emotions significantly mediates the relationship between sales promotion and hedonic consumption on impulse buying.